Accessing Care: Experiences of Minoritised Ethnic Communities - Helen Richards; Liz Parsons; Emma Heeley; James Edward Hill; Cath Harris (The Practising Midwife, 2025)
Spotlight commentary on: Sharma E, Tseng PC, Harden A, Li L, Puthussery S. Ethnic minority women’s experiences of accessing antenatal care in high income European countries: a systematic review. BMC Health Serv Res. 2023;23(1):612. https://doi.org/10.1186/s12913- 023-09536-y. Key points Women from minoritised ethnic communities report difficulties in understanding and navigating the healthcare system and experience stigmatising and discriminatory interactions with care providers which can affect uptake of care. Information and communication are important factors in enabling access to services for women from minoritised ethnic communities. Where possible global majority women from minoritised ethnic communities should be offered enhanced midwife-led continuity of care to improve maternity outcomes.